DYNAMICS OF THE PENITENTIARY SYSTEM, TRANSPARENT AND ACCOUNTABLE HANDLING OF CRIMINAL CASES IN CRIMINAL EXECUTION LAW IN SOUTHEAST ASIA: CONVERGENCE AND DIVERGENCE OF INTERNATIONAL PERSPECTIVES - Widyawati, Anis; Adhari, Ade; Masyhar, Ali; Deo Syahputra, Bearlly; Purnomo, Didik (Indonesia Law Review, 2025)
This research examines the dynamics of the penitentiary system transparent, and accountable criminal case handling in criminal execution law in Southeast Asia, focusing on the convergence and divergence of international perspectives. These countries have diverse approaches to the penitentiary system and criminal law enforcement, including in terms of the implementation of the death penalty and the treatment of prisoners. Some countries, such as Singapore and Malaysia, maintain strict death penalty practices, which often contradict international human rights standards, while others such as the Philippines show inconsistencies in implementing criminal execution laws. This research also examines the three main stages in the enforcement of the penitentiary system, namely the formulation stage, the application stage and the execution stage, which vary across Southeast Asian countries. Historical, political and cultural factors contribute to these variations, affecting the conformity of national legal systems with transparent and accountable international criminal law. In addition, this study highlights the importance of transparency and accountability in criminal case handling, as well as the role of rehabilitation in the penitentiary system, as an effort to align with international standards, especially regarding the treatment of death row prisoners. Understanding these dynamics is expected to provide insight into the differences and similarities in criminal execution laws in Southeast Asia as well as efforts towards better integration with international perspectives on human rights and criminal executions.